2011
DOI: 10.1167/iovs.10-6019
|View full text |Cite
|
Sign up to set email alerts
|

Outflow Physiology of the Mouse Eye: Pressure Dependence and Washout

Abstract: Mouse eyes are similar to human eyes, in that they have no detectable washout rate and a linear pressure-flow relationship over a broad range of intraocular pressures. Because of the absence of washout and the apparent presence of a true Schlemm's canal, the mouse is a useful model for studying the physiology of the inner wall of Schlemm's canal and the conventional outflow tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(143 citation statements)
references
References 14 publications
9
131
3
Order By: Relevance
“…21 Perfusion of mouse eyes ex vivo, where stepped pressure readings are used to strip out conventional (pressure sensitive) from alternative (pressure insensitive) outflow, showed no changes in conventional outflow facility after or during flow readings at moderate pressures, that is, 8-35 mm Hg. 22 In these relatively short-term studies (20-min perfusions at each pressure level with a total study of only a few hours), no IOP homeostatic changes were observed and the return to low (15 mm Hg) pressure value was approximately the same as the initial value at that pressure. [22][23][24] In one study, similar facilities were obtained in the same mouse when anesthetized compared with when euthanatized.…”
Section: Short-term Moderate Pressure Responsesmentioning
confidence: 81%
See 1 more Smart Citation
“…21 Perfusion of mouse eyes ex vivo, where stepped pressure readings are used to strip out conventional (pressure sensitive) from alternative (pressure insensitive) outflow, showed no changes in conventional outflow facility after or during flow readings at moderate pressures, that is, 8-35 mm Hg. 22 In these relatively short-term studies (20-min perfusions at each pressure level with a total study of only a few hours), no IOP homeostatic changes were observed and the return to low (15 mm Hg) pressure value was approximately the same as the initial value at that pressure. [22][23][24] In one study, similar facilities were obtained in the same mouse when anesthetized compared with when euthanatized.…”
Section: Short-term Moderate Pressure Responsesmentioning
confidence: 81%
“…22 In these relatively short-term studies (20-min perfusions at each pressure level with a total study of only a few hours), no IOP homeostatic changes were observed and the return to low (15 mm Hg) pressure value was approximately the same as the initial value at that pressure. [22][23][24] In one study, similar facilities were obtained in the same mouse when anesthetized compared with when euthanatized. 24 In addition, short-term mechanical stretching lasting less than 6 h does not trigger any homeostatic response, as judged by biochemical readouts.…”
Section: Short-term Moderate Pressure Responsesmentioning
confidence: 81%
“…Our findings that hemizygosity for Tek is sufficient to cause disease in mice and that heterozygosity for LoF mutations is associated with PCG of varying severity in patients suggest, for the first time to our knowledge, that there exists a dosage sensitivity for reduced activity of the receptor. It is reported that the conventional outflow path for AH drainage (i.e., SC) plays a less important role in mice than in humans, underscoring the significance of finding elevated IOP in the hemizygous mouse model and suggesting similar structural defects in SC would cause more severe disease in patients (57)(58)(59). Finally, our data indicate that TEK "dose" might be particularly important for proper development of the vasculature of the anterior chamber of the eye, suggesting that regulation of TEK signal strength may be a therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…1). From the anterior chamber AH leaves the eye and enters the general venous circulation by bulk flow by two exit pathways, both commencing at the anterior chamber angle (Johnson, 2005;Lei et al, 2011;Nilsson, 1997;Sihota, 2011).…”
Section: Drainage Of Aqueous Humormentioning
confidence: 99%